DETERMINAN TRANSPARANSI INFORMASI KEUANGAN PADA LAMAN RESMI PEMERINTAH DAERAH PROVINSI DI INDONESIA TAHUN 2016-2018 - Ekrak Puji Lestari; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2020)
This research aimed to analyze the effect of components of characteristics, complexity and quality of financial statements on the transparency of regional financial information. The dependent variable in this research is the transparency of regional financial information on the website of regional government in Indonesia in 2016-2018 which is proxied by the accessibility index of the official government website. The sample used in this transparency study was 33 provincial governments for three years in a row. The research hypothesis testing was performed using panel data regression analysis with Eviews 10 software. This research results show that only the OPD variable has a significant effect on the transparency of regional financial information. While the size of the local government, the level of dependency, population and the results of BPK's audit opinion are positively related which do not have a significant influence on the transparency of regional financial information. This research also proves that the number of findings in the regional government financial statements has a negative and not significant effect on transparency on the official website of the local government.